Induced mutation breeding for qualitative and quantitative traits and varietal development in medicinal and aromatic crops at CSIR-CIMAP, Lucknow (India): past and recent accomplishment. (1st December 2020) - Lal, Raj K.; Chanotiya, Chandan S.; Gupta, Pankhuri
Abstract: Purpose: The nature and kind of some successful mutations achieved through gamma radiation at CSIR-CIMAP, Lucknow are reviewed and described in this article. Medicinal and aromatic crops (MACs) came under the mutation-breeding program very late – perhaps during the 1980s in India. Nevertheless, successes have been glaring and unique too. The plant breeders of the Institute concerted attempts were made for the genetic restructuring of the plant-frame in Hyoscyamus niger L. (black henbane) and Cymbopogon martinii (palmarosa), enhanced alkaloid biosynthesis in henbane, weak, or lack of latex biosynthesis in Papaver somniferum L. (Opium poppy), increased productivity of seeds in Plantago ovata F. (isabgol), and new/increased formation of essential oils in Chamomila recutita [L.] Rauschert (Chamomile) and Cymbopogon winterianus (Java citronella). Several qualitative macro mutations were generated for commercial exploitation, e.g. an unbranched (Ub) and physiologically most efficient variety Aekla and high tropane alkaloid bearing variety Aela of H. niger, opium less oil-seed variety Sujata of opium poppy, a dwarf mutant and a male sterile (ms) line of palmarosa, and new compound yielding variety of chamomile and geranium. Conclusions: The ample quantitative variation was also created by reshuffling the polygenic background in both seed and vegetatively propagated MACs, and subsequently, with applying mutation breeding approach superior varieties were evolved and released after a rigorous screening in the field-evaluation or under pipeline for release. These varieties are Niharika and Mayuri of psyllium; Vallary, CIMAP Sammohak, CIM Ujjwala, and YEL (yellow) of German chamomile and Manjari and CIM Jeeva of Java citronella. Graphical Abstract: